Cycle threshold values are inversely associated with poorer outcomes in hospitalized patients with COVID-19: a prospective, observational cohort study conducted at a UK tertiary hospital. (October 2021) - Wright, Jenny; Achana, Felix; Diwakar, Lavanya; Semple, Malcolm G.; Carroll, Will D.; Baillie, Kenneth; Thompson, Christopher; Alcock, Alice; Kemp, Timothy S.
Highlights: A multi-variable regression analysis of data for hospitalized patients with coronavirus disease 2019 was undertaken. The likelihood of death and cycle threshold (Ct) values at admission were studied. Adjustments were made for known clinical risk factors for the disease. Lower Ct values were associated with poorer outcomes in hospitalized patients. ABSTRACT: This single-centre observational study demonstrated that lower cycle threshold (Ct) values (indicating higher viral loads) on admission to hospital were associated with poorer outcomes in unvaccinated, hospitalized patients with coronavirus disease 2019 (COVID-19). Demographic and outcome data were collected prospectively for all adult patients who tested positive for severe acute respiratory syndrome coronavirus-2 on admission to the University Hospitals North Midlands NHS Trust between 1 February and 1 July 2020. Nasopharyngeal swab samples were obtained, and a valid Ct value was determined for all patients using the Viasure reverse transcription polymerase chain reaction assay, validated by Public Health England, on admission to hospital. Multi-variable logistic regression results based on data from 618 individuals demonstrated a significant inverse relationship between the odds of death and Ct values (adjusted odds ratio 0.95, 95% confidence interval 0.92–0.98, P =0.001). The association remained highly significant after adjusting for known clinical risk factors for COVID-19